How social media platforms enhance user engagement in organizational contexts: A systematic literature review - Lin, Lin; Van Zoonen, Ward; Koehnlein, Christian; Moser, Klaus (58th Hawaii International Conference on System Sciences, 2025)
Companies use both organization-specific (internal) and public social media platforms to enable interactions between their employees and customers. However, continued user engagement on these platforms often proves challenging. This study reviews factors influencing user engagement in organizational contexts. Technological features, individual characteristics, and organizational factors are examined. A systematic literature review identified, analyzed, and discussed 39 research papers. The results show that all three groups of determinants influence user engagement. In the internal organizational context, mobile platform availability and management support play a significant role. In the marketing context, platform features, individual motivations, and types of content are essential. Increased user engagement can positively affect employees’ performance and customers’ purchase intention, so the continued management and use of social media platforms are critical to a company's succes
Keywords: organizational social media; user engagement; technological features; individual characteristics; organizational factors